THE IMPLEMENTATION LEVEL OF BIOSECURITY IN LAYER CHICKEN FARMING IN SENGANAN VILLAGE, TABANAN BALI - Suputra, I Ketut Bayu; Sukada, I Made; Wandia, I Nengah; Mufa, Romy Muhammad Dary (Buletin Veteriner Udayana, 2025)
Biosecurity is a crucial aspect of layer poultry farming to prevent the spread of diseases that can cause economic losses. This study aims to evaluate the level of biosecurity implementation in layer poultry farms in Senganan Village, Penebel District, Tabanan Regency. The research employed a survey method with a cross-sectional approach, collecting data through direct interviews with 24 farmers using a questionnaire. The results of the study showed that the application of biosecurity on laying hen farms in Senganan Village was categorized as lacking for the isolation aspect (36.66%), good for the traffic control aspect (60%), and sufficient for the sanitation aspect (50.83%). Farmers' awareness of the importance of biosecurity is relatively high (75.83%); however, its application remains suboptimal, particularly in isolating newly arrived and sick chickens. These findings highlight the need to strengthen education and technical guidance for farmers, particularly in the application of isolation and sanitation practices, to improve disease control efficiency and ensure the sustainability of layer poultry farming operations.